(3GdeSGFds - (3CHh jhSa jYbhH Hf Ydj GdbQTj GdbUQGfj, GdbUQGfj,J (B200 (3g` s ((3eUWai NhLg Hf bGSe GdeUQi s)
(3ChdgG (B:s
(3cGf ai Ref GdfHi Udi Gddg Ydjg hSde TGH eSQa Ydi faSg adeG Jhai bGd Udi Gddg Ydjg hSde ddUMGHI UdGI GdeSQa aJYLH GdUMGHI hde jJcdehG s
(3BNQgG (B:s
(3Je GdcJGH HYhf Gdedc GdhgGH s
(3HgG LOGhd JhVjMjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B122s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1669s
Keywords: (3Gdadcs